REPRESENTASI BRAND AMBASSADOR LAKI-LAKI PADA PRODUK KECANTIKAN - Indinabila, Yunita; Ulyan Nasri; M. Gufran; M. Mizanul Haq; Nurdiah (Jurnal Spektrum Komunikasi, 2024)
The traditional representation of women in beauty products has often focused on their attention-grabbing appearance, while men have typically been associated with a simpler, more masculine look. However, this discourse is evolving as more beauty brands use male brand ambassadors. This shift is due to the growing acceptance of men using beauty products, despite some resistance rooted in societal stereotypes. This study aims to analyze how male brand ambassadors challenge traditional gender norms, particularly regarding masculinity and femininity. Using discourse analysis, the research examines advertisements featuring male brand ambassadors and explores how they simultaneously project both masculinity and femininity. The results show that these advertisements reflect a changing perception of gender roles, where men are portrayed as not only masculine but also in touch with femininity, blurring the boundaries between the two. This research contributes to the understanding of how beauty marketing reflects and influences evolving gender identities and the shifting cultural landscape of beauty standards.